Ion channel trafficking implications in heart failure - Reisqs, Jean-Baptiste; Qu, Yongxia Sarah; Boutjdir, Mohamed (Frontiers in Cardiovascular Medicine, 2024)
Heart failure (HF) is recognized as an epidemic in the contemporary world, impacting around 1%–2% of the adult population and affecting around 6 million Americans. HF remains a major cause of mortality, morbidity, and poor quality of life. Several therapies are used to treat HF and improve the survival of patients; however, despite these substantial improvements in treating HF, the incidence of HF is increasing rapidly, posing a significant burden to human health. The total cost of care for HF is USD 69.8 billion in 2023, warranting a better understanding of the mechanisms involved in HF. Among the most serious manifestations associated with HF is arrhythmia due to the electrophysiological changes within the cardiomyocyte. Among these electrophysiological changes, disruptions in sodium and potassium currents’ function and trafficking, as well as calcium handling, all of which impact arrhythmia in HF. The mechanisms responsible for the trafficking, anchoring, organization, and recycling of ion channels at the plasma membrane seem to be significant contributors to ion channels dysfunction in HF. Variants, microtubule alterations, or disturbances of anchoring proteins lead to ion channel trafficking defects and the alteration of the cardiomyocyte's electrophysiology. Understanding the mechanisms of ion channels trafficking could provide new therapeutic approaches for the treatment of HF. This review provides an overview of the recent advances in ion channel trafficking in HF.